Individual and Organizational Factors in Coping With COVID-19 in Soldier Students - Talić, Irma; Einhorn, Alina; Renner, Karl-Heinz (Frontiers in Psychology, 2022)
The COVID-19 pandemic has posed significant burden across different industrial sectors. Generally, an increase in psychological stress experiences has been reported, while the stress and coping responses of specific, potentially burdened populations have received less attention thus far. Thus, the present study investigated relations between individual (i.e., extraversion, neuroticism, conscientiousness) and organizational (i.e., organizational commitment and study satisfaction) factors, indicators of psychological health (i.e., loneliness, life satisfaction, COVID-19-related stress), and possible mediating effects of four broad coping dimensions (active coping, avoidant coping, social support, positive cognitive restructuring) in a specific sample of soldier students who engage in a double-role being military affiliates and students of non-military subjects. To this end, we assessed data of soldier students at two measurement points (N = 106 at t1 and N = 63 at t2) shortly after the second national lockdown in Germany (20. May 2021 to 11. July 2021) during the COVID-19 pandemic. Personality traits showed expected associations with indicators of psychological health, i.e., positive relations between neuroticism and social loneliness, between extraversion and COVID-19 stress, and negative relations between neuroticism and life satisfaction. Remarkably, organizational variables showed effects above and beyond personality traits on loneliness and life satisfaction. Neither individual, nor organizational factors could predict change in psychological health over time. We found evidence for mediation effects through active coping, avoidant coping, and the use of social support, but not through positive cognitive restructuring. Findings highlight the relative importance of organizational factors besides personality traits for psychological health in a military student sample, holding important implications for designing efficient support systems in the military.